Międzynarodowe opodatkowanie emerytur – ujęcie modelowe - Lipniewicz, Rafał (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
Along with the changing demographic structure of many countries, especially developed ones, one of the significant social groups are people who receive benefits from old-age security. One aspect of this phenomenon is the issue of taxation of financial benefits received by pensioners in cross-border situ¬ations, in particular when during retirement pensions are paid out of a fund located in the territory of a different country from the one in which the beneficiary resides (tax residence). The taxpayer’s right to tax such pensions is subject to negotiations between states that intend to conclude a double tax treaty, in which they will allocate tax power in this matter. These agreements are modeled on model conventions developed by the OECD and the UN. The purpose of this article is to analyze the legal, economic and administrative aspects resulting from modeled in the model conventions ways of allocating tax rights between the source of pension payment and the residential country of such a benefit
Keywords: pensions; double taxation; residence principle; source principle